Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1073/pnas.0807167105
|View full text |Cite
|
Sign up to set email alerts
|

DEET repels ORNery mosquitoes

Abstract: D EET ([N-N]-diethyl-m-toluamide) is widely used around the world as a repellent for mosquitoes and other biting insects. It was originally identified by a structure-activity study using synthetic compounds (1). Recently, a number of new compounds with similar activity [e.g., picaridine (2)] have been identified, but DEET remains the gold standard. Despite a tremendous number of studies (3), however, a plausible and evidence-based mechanism for DEET's action has remained elusive. In a recent study, Ditzen et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 8 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…Repellency can help describe the behavioral effects that alter the perception of the peripheral nervous system (PNS), which leads to the insect neither biting nor sucking and causes them to move away from their food source [40]. Thus, repellency is a strategy to prevent reinfection of host by an ectoparasite but does not result in the death of the insect.…”
Section: Repellentmentioning
confidence: 99%
“…Repellency can help describe the behavioral effects that alter the perception of the peripheral nervous system (PNS), which leads to the insect neither biting nor sucking and causes them to move away from their food source [40]. Thus, repellency is a strategy to prevent reinfection of host by an ectoparasite but does not result in the death of the insect.…”
Section: Repellentmentioning
confidence: 99%
“…For example, several studies have shown that DEET can interfere with olfactory receptor neurones that are tuned into detecting semiochemicals that induce and facilitate host seeking behaviour in mosquitoes [6], [7]. Other studies have shown that DEET is actively detected by olfactory receptor neurones on the antennae or maxillary palps [8], [5]. These studies highlight the fact that mosquito repellents may involve more than one mode of action.…”
Section: Introductionmentioning
confidence: 99%
“…DEET was identified more than 50 years ago by a structure-activity study of synthetic compounds and, although a number of compounds with similar activity have been identified, their efficacy is often judged by comparison with DEET (2). The mode of action of DEET has not been elucidated fully.…”
mentioning
confidence: 99%